PENGARUH STRATEGI KEMITRAAN DAN MANAJEMEN MUTU UNTUK MENINGKATKAN KEUNGGULAN BERSAING DAN KINERJA PERUSAHAAN DALAM PEMENUHAN TANDAN BUAH SEGAR (TBS) DI PT.PERKEBUNAN NUSANTARA V - Sumarti, Sumarti; Isyandi, B.; Samsir, Samsir (Komunitas Manajemen Kompetitif, 2025)
This research aims to examine and analyze the influence of partnership patterns and quality management on competitive advantage. To test and analyze the influence of partnership patterns and quality management on company performance. To test and analyze the influence of competitive advantage on company performance. To examine and analyze the influence of partnership patterns and quality management on company performance in meeting the supply of Fresh Fruit Bunches (FFB) through competitive advantage. The population in this study was 185 people. The total sample was 185 people. The data used in this research are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysis method used in this research is Structural Equation Modeling (SEM). The research results show that partnership patterns influence the competitive advantage variable. Quality management influences competitive advantage. The partnership pattern has no effect on company performance. Quality management influences company performance. Competitive advantage is an important variable that is the main capital in business so that it influences the company's performance variables. Partnership patterns have a significant effect on company performance through competitive advantage. Quality management has a significant effect on company performance through competitive advantage